The pottery production from Hegra/Madāʾin Sālih (Saudi Arabia) during the Nabataean period. Preliminary results, 2008-2011 - Durand, Caroline; Gerber, Yvonne (Proceedings of the Seminar for Arabian Studies, 2014)
Madāʾin Sālih — the ancient city of Hegra — in north-western Saudi Arabia was an important site located on the southern edge of the Nabataean kingdom, and a stop on the south-east-north-west caravan route running from South Arabia to the Mediterranean coast. Since 2008 the archaeological remains in Hegra have been the object of yearly excavations by a French-Saudi archaeological team investigating different areas of the site: the Urban centre with its city wall, the Sacred area of the so-called Jabal Ithlib, and several rock-cut tombs. Good stratigraphical sequences within the Urban centre were yielded by several trenches, showing pottery dating from the Hellenistic period to the sixth–early seventh century AD. The French-Saudi excavations in Hegra yielded archaeological evidence of occupation prior to the Nabataeans in the area of the Urban centre, presumably linked to the neighbouring city of Dedan/Khurayba; a large pottery manufacture on the site of Hegra during the Nabataean period, still of strong local pottery tradition; continuous contact with Petra, the Nabataean capital, during Nabataean predominance in the area and Nabataean control of the trade routes (second half of the first century BC-early second century AD); long-distance trade connections with the Mediterranean area and with the Mesopotamian region; all together enlightening the key role of Hegra in trans-Arabian caravan routes.